2011
DOI: 10.1007/s12052-011-0371-0
|View full text |Cite
|
Sign up to set email alerts
|

Why Don’t People Think Evolution Is True? Implications for Teaching, In and Out of the Classroom

Abstract: The causes of non-acceptance of evolution are groupable into five categories: inadequate understanding of the empirical evidence and the content of modern evolutionary theory, inadequate understanding of the nature of science, religion, various psychological factors, and political and social factors. This multiplicity of causes is not sufficiently appreciated by many scientists, educators, and journalists, and the widespread rejection of evolution is a much more complicated problem than many of these frontline… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
30
0
10

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 189 publications
(238 reference statements)
0
30
0
10
Order By: Relevance
“…It has also been reported that the intermediate positions, between creation only and evolution, are perceived suspiciously by some (Allmon 2011;Preseten and Epley 2009). Allmon (2011) states that the 'accommodated positions' (intermediate positions) have critics from both, religious and non-religious, sides.…”
Section: Introductionmentioning
confidence: 95%
See 3 more Smart Citations
“…It has also been reported that the intermediate positions, between creation only and evolution, are perceived suspiciously by some (Allmon 2011;Preseten and Epley 2009). Allmon (2011) states that the 'accommodated positions' (intermediate positions) have critics from both, religious and non-religious, sides.…”
Section: Introductionmentioning
confidence: 95%
“…Although most leaders of mainstream religion have largely acknowledged that there is no substantial conflict between the ToE and their religious percepts (Zimmerman 2010) many individuals still have issues with accepting the ToE (Mansour 2008;Smith 2010 a, b;Allmon 2011) and relating it to their religious views (Meadows, Doster and Jackson 2000;Chandi and Mancy 2011).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…As Shtulman (2006) notes, this may not be a deeplyconsidered response, because "those who do not endorse the claim that Darwin's theory of evolution has been well supported by evidence tend to endorse the alternative claim (i.e., that Darwin's theory of evolution has not been well supported by evidence) rather than plead ignorance". Furthermore, lack of knowledge of the evidence for evolution is clearly not necessarily the only, or even the most important, reason for lack of acceptance of evolution (Allmon 2011;Shtulman 2011;Nadelson 2012, 2013;Rosengren et al 2012;Dunk et al 2017). …”
Section: Introductionmentioning
confidence: 99%